275 "MOVING ON UP": FEASIBILITY OF A WARD-BASED THERAPY INITIATIVE TO IMPROVE PATIENT ACTIVITY LEVELS IN NEUROLOGICAL REHABILITATION. (25th October 2022) - Doran, N; Murphy, R; Clarke, E; Quigley, S; Kiernan, S; Malone, A
Abstract: Background: Patients admitted for neurological rehabilitation are not receiving sufficient dosage of activity to facilitate optimal recovery. Previous research has reported issues with feasibility and patient adherence to intensity programs. Methods: Mixed methods were employed for this feasibility study. The "Moving On Up" program encompassed "Activitea" structured practice of sit to stands prompted by mealtimes, "Step It Up" a gradual walking program using pedometers and "Weekend Workout" increasing practice of exercise programs. These activities were in addition to daily therapy sessions over a four-week intervention period. Primary feasibility outcomes investigated recruitment, retention, adherence, adverse events, facilitators, barriers and acceptability of the program and preliminarily assessed changes in activity levels using the ActivPAL accelerometer. Functional tests assessed mobility, health-related quality of life and fear of falls. Descriptive statistics were used for analysing quantitative data. Braun and Clarke's thematic analysis was adopted when reviewing qualitative data. Results: Ten participants were recruited with zero dropouts. Median age was 72 years and five had a diagnosis of brain tumour excision. Eight participants demonstrated excellent adherence with completion of daily activity logs. There was one participant non-injurious fall, no other adverse events. Clinical outcomes demonstrated improvement in median daily step count, stepping and standing time. The median daily step count for the group increased from 1, 375 steps (IQR 2, 867, range 82-4, 248) to 1, 724 steps (IQR 2, 914, range 80-8, 207). All functional tests improved. Seven participants and three therapists completed semi-structured interviews. Five themes emerged; motivation to move more, empowerment, barriers to increasing activity, weekends long and boring and job satisfaction. Conclusion: The "Moving On Up" program was feasible to implement without additional staffing and was accepted by key stakeholders. Future research is warranted into the program's effectiveness, incorporating a larger sample and randomised pilot trial. Inclusion of a follow-up of participants after discharge would be desirable to investigate long-term effects on activity.